Some 3-(Arylimino)-5-(/V-benzylidenehydrazono)-1,2,4-dithiazolidines. Oxidative Debenzylation and Cyclization of 5-Aryl-1 - (benzylideneamino)-2- S -benzyliso-2,4-dithiobiurets - All M.R.; Singh R.; Verma V.K. (My University, 2025)
Synthesis of 3-(aryllmlno)-5-(A/-benzylldenehydrazono)-1,2,4-dlthlazoll-dlnes (IVa-e) has been achieved by the oxidative debenzylation and cycllzation of the corresponding 5-aryl-1-(benzylldeneamlno)-2-S-benzyllso-2,4-dlthlobiurets (IIa-e). These dihlazolidlnes have been characterized by their preparation from the corresponding 2,4-dlthloblurets (Illa-e) and also by IR spectra. © 1983, American Chemical Society. All rights reserved.